Vesical Varices: An Unusual Cause of Hematuria - Baby, Akhil; Singhal, Praveen; Ahmed, Nisar; Singh, Shobhit; Philips, Cyriac Abby; Rajesh, Sasidharan (Journal of Gastrointestinal and Abdominal Radiology, 2024)
Portal hypertension is a common complication of cirrhosis and may lead to the formation of venous collateral channels. Usually, varices due to portal hypertension develop in the lower esophagus, stomach, rectum, or other parts of the digestive tract. Extraintestinal ectopic varices are rare. Here, we present a patient with ectopic urinary bladder varices, who presented with hematuria and symptomatic anemia. The bleeding was managed with minimally invasive endovascular approach.
Keywords: bladder; ectopic; schistosomiasis; albumin; cirrhosis; glue